Overeducation: evidence from Portugal - Custódio, António José Ribeiro da Silva dos Santos (2013)
The levels of educational attainment have risen strongly over the last thirty years in Europe. In Portugal, the education system, particularly the higher education sector, expanded in late 80s. Parallel to this expansion have been growing up concerns about the incidence of overeducation in Portuguese labour market. This study presents an extensive review of literature about overeducation and ways of measuring the phenomenon, as well an evolutive description on higher education in Portugal and some recent developments at European and National level. The study was based on objective and empirical approach, focusing overeducation as a form of underutilization of educational skills and linking worker’s formal education with the skills required to perform a job. Using the 1998, 2004 and 2009 data from Labour Force Survey collected by Office of National Statistics (INE), the present study analysed overeducation in Portugal, aiming to identify and quantify the existence of the phenomenon during the considered period. The study results revealed the existence of overeducation over the period, along with an increase of incidence, which varies with gender and being more relevant on women.